AUDITORY ACUITY IN DIABETES MELLITUS TYPE II: A CASE–CONTROL STUDY - SHREYAS S JOSHI; SANTOSH BIRAJDAR; RAJESH A KARAMBELKAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of the study was to analyze the status of auditory acuity in patients with Type II diabetes mellitus (DM) as compared to healthy individuals of comparable age groups using pure tone audiometry. Methods: This was a case–control study in which 80 known cases of DM were enrolled as cases (Group D) and a similar number of age-matched healthy individuals were included as the control group (Group N). Demographic details such as age and gender were compared. A detailed history was taken and a general and systemic examination was done. Pure tone audiometry (250Hz, 500Hz, 1000Hz, 2000Hz, 4000Hz, 6000Hz, and 8000 Hertz frequencies) was done in all the patients, and air conduction and bone conduction of both the ears were determined. SSPE 21 software was used for statistical analysis. p<0.05 was considered to be statistically significant. Results: Both groups were found to be comparable in terms of gender and age distribution with no statistically significant difference (p<0.05). Mean fasting and postprandial blood sugar levels as well as HbA1c were found to be higher in Group D as compared to Group N and the difference was highly significant (p<0.0001). In Group D (Diabetic patients), mild, moderate, and severe sensorineural hearing loss (SNHL) at speech frequency was seen in 31 (38.75%) whereas moderate and severe SNHL was seen in 22 (27.50%) and 18 (22.50%) patients. In Group N (Non-diabetic), 5 (6.25%) patients had mild SNHL and moderate and severe hearing loss was not seen in any of the patients. The mean hearing threshold (Both Ears) for bone as well as air conduction was found to be more in Group D as compared to Group N at all frequencies and the difference was statistically significant (p<0.05). Conclusion: Individuals with Type II DM are found to have an increased incidence of subclinical hearing loss. This subtle hearing loss may go undetected for a considerable period of time and hence regular audiometric evaluation is required for early diagnosis of subclinical hearing loss in patients of DM.